Preoperative misdiagnosis analysis and accurate distinguish intrathymic cyst from small thymoma on computed tomography - Li, Xin; Han, Xingpeng; Sun, Wei; Wang, Meng; Jing, Guohui; Zhang, Xun (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: To evaluate the role of computed tomography (CT) in preoperative diagnosis of intrathymic cyst and small thymoma, and determine the best CT threshold for distinguish intrathymic cyst from small thymoma. Methods: We retrospectively reviewed the medical records of 30 patients (17 intrathymic cyst and 13 small thymoma) who had undergone mediastinal masses resection (with diameter less than 3 cm) under thoracoscope between January 2014 and July 2015 at our hospital. Clinical and CT features were compared and receiver-operating characteristics curve (ROC) analysis was performed. Results: The CT value of small thymoma [39.5 HU (IQR, 33.7–42.2 HU)] was significantly higher than intrathymic cyst [25.8 HU (IQR, 22.3–29.3 HU), P=0.004]. When CT value was 31.2 HU, it could act as a threshold for identification of small thymoma and intrathymic cyst (the sensitivity and specificity was 92.3% and 82.4%, respectively). The ΔCT value of enhanced CT value with the non-enhanced CT value was significantly different between small thymoma [18.7 HU (IQR, 10.9–19.0 HU)] and intrathymic cyst [4.3 HU (IQR, 3.0–11.7 HU), P=0.04]. The density was more homogenous in intrathymic cyst than small thymoma, and the contour of the intrathymic cyst was more smoothly than small thymoma. Conclusions: Preoperative CT scans could help clinicians to identify intrathymic cyst and small thymoma, and we recommend 31.2 HU as the best thresholds. Contrast-enhanced CT scans is useful for further identification of the two diseases.